Are the infrared thermography findings skin temperature‐dependent? a study on neck pain patients. Issue 1 (1st October 2012) - Zaproudina, Nina; Airaksinen, Olavi; Närhi, Matti
<x xml:space="preserve">Abstract</x> Background Skin temperature (Tsk) disorders have been proposed as sign of impaired innervation in several conditions, but the influence of different factors on the infrared thermography (IRT) findings remains unclear. Methods The relations between the Tsk and δT (side‐to‐side temperature difference) values, and influence of age, gender, anthropometric characteristics and pain intensity on those values were analysed in non‐specific neck pain (NP) patients (n = 91) using mixed model analysis. IRT findings were also compared in subgroups of NP patients: with cold (CHNPP, n = 21) or warm hands (WHNPP, n = 56) and healthy controls, with cold (CHC, n = 11) or warm hands (WHC, n = 19). Also, the stability of δT values in CHNPP was examined. Results Only the area of measurement and the actual Tsk influenced the δT values. CHNPP demonstrated higher δT values in distal parts, compared with WHNPP and controls, but those values vanished when their hands turned warm. δT values in CHNPP were related to the pain intensity. The findings of WHNPP and WHC did not differ. Conclusion Our results suggest that the δT values as signs of impaired Tsk regulation are dynamic and better detectable in cold skin. The results underline the need of caution in interpretation of IRT findings.